Penyusunan Laporan Keuangan Berdasarkan SAK EP dan ISAK 335 pada Masjid Jami Nurul Yaqin - Rini Fatimah; Nuramalia Hasanah; Hera Khairunnisa (Indo Publishing, 2026)
This study aims to prepare financial statements based on SAK EP and ISAK 335 for the Nurul Yaqin Jami Mosque and to develop guidelines for preparing financial statements. The method used in this study is qualitative with a descriptive approach, and the research type is Research and Development (R&D) using the ADDIE model, limited to the Analysis, Design, and Development stages. In this study, the Jami Nurul Yaqin Mosque was selected as the research subject. Primary data was obtained through interviews with the mosque’s chairman and treasurer, while secondary data was obtained from documentation in the form of the organizational structure and the 2024 cash receipts and disbursements report. Data analysis was conducted through several stages, namely data reduction, data presentation, and drawing conclusions. The results of this study produced financial statements for the Jami Nurul Yaqin Mosque based on SAK EP and ISAK 335 using Microsoft Excel, consisting of a statement of financial position, a statement of comprehensive income, a statement of changes in net assets, a cash flow statement, and notes to the financial statements. In addition, this study produced guidelines for preparing financial statements based on SAK EP and ISAK 335 using Microsoft Excel, which can serve as a reference for the management of the Jami Nurul Yaqin Mosque in preparing financial statements independently. This study also recommends that future research proceed to the Implementation and Evaluation stages to test the effectiveness of the guidelines that have been developed.